PENGEMBANGAN BOOKLET BERBASIS ETNOSAINS PADA JAJANAN JENANG AYAS UNTUK MENINGKATKAN LITERASI SAINS SISWA - Magfiroh, Puteri Hidayatul; Rakhmawan, Aditya; Yamin, Yamin; Hartiningsih, Try; Mulyastuti, Herlina (Natural Science Education Research, 2025)
This development research aims to produce an ethnoscience-based booklet on jenang ayas snacks and to determine the validity, readability, student responses and improvement of science literacy towards ethnoscience-based booklets. This type of Research n Development (RnD) research, using the ADDIE model. Sampling using a side purposive teahnique. The population in this study were all students of class VIII of SMP 31 Gresik with a sample of class VIII-C. The instrument used were validation sheets media, material experts, readability questionnaires, responses, and science literacy questions. The result of the study showed that the ethnoscience-based booklet on jenang ayas snacks that was developed was included in the very valid category for use, seen from the results of media expert validation of 94,03%, material expert validation of 96,53%, readability questionnaire of 88,92%, student response questionnaire of 88,45%, and an increase in science literacy on N-Gain of 0,69. These result indicate that ethnoscience-based booklets on jenang ayas snacks is effective in improving student’s science literasy.